EVALUASI PEMERIKSAAN JENTIK BERKALA RUMAH WARGA DI WILAYAH PUSKESMAS TANAH KALIKEDINDING SURABAYA - Rina Tri Agustini (Universitas Airlangga, 2015)
During of January 2015 Dengue Hemorrhagic Fever (DHF) took place in 37 County city in East Java province, which the number of cases were 3136 and mortality rate were 52 cases. Surabaya reached 59 cases of DHF. The number of Larva Free Index in Tanah Kalikedinding Public Health Center bas around 86–88.7% in 2015, so haven’t reached the specified target which is 95%. One of the activities conducted to improve Larve Free Index was performing Periodic Larva Inspection of houses. Therefore, need to evaluation the implementation of Periodic Larva Inspection of houses included implementer, activities, time of implementation, reporting, and instrument of Periodic Larva Inspection. The Research design observational with study evaluation by descriptive.Technique of collecting data were included interviews, and documents collected. Analyze data by compared data obtained with the existing regulations and guidelines. Evaluation of implementer were in accordance with the regulation. However, if possible have to do advocacy for human resources addition from outside the posyandu cadres and dasawisma groups. Activities aspect underway in accordance with the guidelines. Time of implementation by Larva Monitoring Mother appropriate to standard, while it by Public Health Center offi cers more routine because it is adapted to conditions.Reporting aspect was in accordance with the regulation. Instruments that carried when implementation were accordingly. However, need to use Larva Card in each houses/buildings to facilitate the Inspection and data collecting. In addition, can be apply the Larva Free Village Contest to motivate cadres and citizens.Keywords: DHF, evaluation, larva, Periodic Larva Inspection.